The Evaluation of Websites of Polish Yacht Ports on the West Pomeranian Sailing Route - Barbara OSÓCH (Communications of International Proceedings, 2021)
The location of yacht ports in the cross-border area of ​​the West Pomeranian Voivodeship makes them a component of the region's brand. The surroundings of unique nature act as a magnet for Polish and foreign sailors, attracting more and more of them each year. Therefore, ports information and their surroundings should be presented on their official websites, serving as tourist information and promotion of the region. The main assumption of the article is the assessment of 38 official websites of marinas, yacht ports and ports located on one of the most recognizable shipping routes in Poland and Europe - the West Pomeranian Sailing Route. The methods used include the inventory of websites in terms of determining the existing basic and additional attributes as well as qualitative evaluation of components, i.e. valorization using the scoring method. The aim was to show the usefulness of websites for tourists looking for information about a given facility and services provided. The obtained scores allowed for the segregation of yacht ports and marinas according to the level of website development into 5 classes. All port services show imperfections. Taking the generalization, it can be stated that port services in the immediate vicinity of the Baltic open sea show a higher degree of development than those located inland along the Odra River, surrounded by Lake Dąbie and the Szczecin Lagoon.
Keywords: Web Services; Assessment; Marinas; Sailing Route.